2021
DOI: 10.1093/cid/ciab167
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of 16S Ribosomal RNA Gene Polymerase Chain Reaction/Sanger Sequencing in Clinical Practice

Abstract: Background Accurate microbiologic diagnosis is important for appropriate management of infectious diseases. Sequencing-based molecular diagnostics are increasingly used for precision diagnosis of infections. However, their clinical utility is unclear. Methods We conducted a retrospective analysis of specimens that underwent 16S ribosomal RNA (rRNA) gene polymerase chain reaction (PCR) followed by Sanger sequencing at our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
2
26
2
Order By: Relevance
“…One recently published retrospective analysis has reported highest yield (37%) in cardiovascular infections. 17 Similarly, another study from Indonesia reported positive nucleic acid amplification test (using 16S ribosomal RNA) with 83.1% sensitivity in AFB smear-negative patients with pulmonary TB. 18 With regard to PD patients, there are a number of case reports where pathogen was detected by 16S ribosomal RNA and cultures were negative.…”
Section: Discussionmentioning
confidence: 94%
“…One recently published retrospective analysis has reported highest yield (37%) in cardiovascular infections. 17 Similarly, another study from Indonesia reported positive nucleic acid amplification test (using 16S ribosomal RNA) with 83.1% sensitivity in AFB smear-negative patients with pulmonary TB. 18 With regard to PD patients, there are a number of case reports where pathogen was detected by 16S ribosomal RNA and cultures were negative.…”
Section: Discussionmentioning
confidence: 94%
“…Prior to the introduction of NGS into the described assay, it was exclusively based on Sanger sequencing, and only samples with Ct values equal or below 32 cycles were sent to sequencing, as described in ( 21 ). Considering the higher sensitivity of NGS, the threshold for sequencing was increased to 34 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA sequencing is a broad-range PCR used in identifying bacterial pathogens to the species level by sequencing the highly-conserved bacterial 16S rRNA region [ 1 , 2 ]. Previous studies have demonstrated this molecular application has reasonable concordance when compared to conventional bacterial cultures and has clinical significance [ 4 , 5 , 6 ]. This technology is especially beneficial, but not limited, to more invasive, difficult-to-diagnose and complicated culture-negative infections where pathogen identification is of high importance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also shown its clinical impact in the management of culture-negative endocarditis [ 12 , 13 , 14 , 15 ]. To date, there is a paucity of data on the clinical utility of 16S rRNA sequencing in pediatric infections [ 2 , 6 ]. Few studies highlight the diagnostic utility of 16S rRNA sequencing in select pediatric infections [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%